THE ROLE OF LEARNING STRATEGIES IN THE PROCESS OF ESP ACQUISITION OF INTENDING EDUCATORS - Dmitrenko, Natalia; Petrova, Anastasiia; Podzygun, Olena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article is dedicated to the problem of using learning strategies in the process of ESP acquisition of intending educators. The authors analyzed the methodological literature on the research topic, on the basis of which the definitions and main characteristics of learning strategies, as well as the implicit and explicit ways of using the strategies in the process of ESP acquisition of intending educators, are presented. R. Oxford’s explicit model of using the instruction-based learning strategies is considered in detail: an algorithm for its use is presented, as well as the basic rules that should be followed in the process of using the model. During the experimental teaching of ESP of intending teachers, R. Oxford’s explicit model of using the instruction-based learning strategies was tested. At the beginning and the end of the experimental training, the questionnaires were conducted to establish the level of proficiency in the learning strategies, as well as the control testing was performed to define the level of ESP acquisition of intending educators. The results of the research confirmed the effectiveness of the used model, which showed an increase in the level of proficiency in the strategies: effective memorization, mental processes, compensatory ability, organization of education and its assessment, management of emotions and collaboration with other students. In turn, the increase in the level of proficiency in the learning strategies was positively reflected in the level of ESP acquisition of intending educators.